2012
DOI: 10.1016/j.jnnfm.2011.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Constant force extensional rheometry of polymer solutions

Abstract: We revisit the rapid stretching of a liquid filament under the action of a constant imposed tensile force, a problem which was first considered by Matta & Tytus [JN-NFM vol. 35, pp 215-229, 1990]. A liquid bridge formed from a viscous Newtonian fluid or from a dilute polymer solution is first established between two cylindrical disks. The upper disk is held fixed and may be connected to a force transducer while the lower cylinder falls due to gravity. By varying the mass of the falling cylinder and measuring i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 50 publications
(90 reference statements)
0
28
0
Order By: Relevance
“…It will be of future interest to see whether degradation in the molecular weight of the MUC5B chains can be systematically monitored and modelled using the finite breakup time derived from the FENE-P model presented herein and tested against results from CaBER experiments. Care must be taken when extracting molecular weight values at various stages of degradation from the values of b extracted from filament thinning measurements, as previous work has shown that the FENE-P model can substantially overpredict the true tensile stress in strong transient elongational flows [29,30]. However, in the quasi-steady FENE limit in which the chains are close to fully stretched, much better agreement with the values expected from molecular theory can be obtained [31].…”
Section: Discussionmentioning
confidence: 99%
“…It will be of future interest to see whether degradation in the molecular weight of the MUC5B chains can be systematically monitored and modelled using the finite breakup time derived from the FENE-P model presented herein and tested against results from CaBER experiments. Care must be taken when extracting molecular weight values at various stages of degradation from the values of b extracted from filament thinning measurements, as previous work has shown that the FENE-P model can substantially overpredict the true tensile stress in strong transient elongational flows [29,30]. However, in the quasi-steady FENE limit in which the chains are close to fully stretched, much better agreement with the values expected from molecular theory can be obtained [31].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, recent experiments to determine the value of extensibility, L, by Szabo et al (2012) using a falling plate technique suggest that in practice this is significantly shorter than suggested by molecular theory. However, these experiments were performed with much higher molecular weight PS than that considered here.…”
Section: Simple Model Of Jettingmentioning
confidence: 95%
“…Underestimation of relaxation time [Clasen et al (2006); Vadillo et al (2012)] and overestimation of extensibility [Szabo et al (2012)] both increase the likelihood of the occurrence of regime III behavior in fast polymer ink-jet printing applications.…”
Section: à11mentioning
confidence: 99%
“…For high viscosity systems, rheometers have been designed by Meissner,1 Münstedt,2, 3 and recently by Sentmanat et al4 that explore the possibilities to mechanically grab and hold a sample. For lower viscosities down to η ≈ 1 Pa · s, filament stretching devices have been developed over the last two decades that rely on the adhesion of a sample to two surfaces between which the fluid is stretched 5–9. For viscosities below 1 Pa · s, recently the capillary breakup extensional rheometer (CaBER) was proposed as a method to determine the transient extensional viscosity as well as the extensional relaxation time of viscoelastic fluids 10–21.…”
Section: Introductionmentioning
confidence: 99%